Application of Concrete Learning Media to Improve Mathe-matics Learning Outcomes of Elementary School Students - silvester sisil; Pebria Dheni Purnasari; Margaretha Lidya Sumarni; Totok Victor Didik Saputro (Business Finance Analyst Co., 2023)
Abstract: This study aims to improve student learning outcomes by applying concrete learning media to mathematics. This research is a type of Classroom Action Research (CAR). The subjects in this study were 27 students of SDN 03 Bengkayang class IV. Data collection techniques used are observation, questionnaires, tests, and documentation. Data analysis techniques using quantitative descriptive. The results of the study show that there is an increase in student learning outcomes by applying concrete learning media. This can be seen from the acquisition of an average pre-cycle value of 50.7 to 81.5 with an N-Gain of 0.6 in the moderate category. By implementing concrete learning media in mathematics, it becomes one of the strategies for solving problems in the teaching and learning proces.